Comportamento mecânico de uma cerâmica Y-TZP: efeito de tratamentos de superfície e técnicas de processamento - Zucuni, Camila Pauleski (2017)
This study is composed by three studies with respective goals: 1st study- to evaluate the effect of post-processing surface treatments (polishing, heat treatment/annealing and glazing), associated or not with autoclave aging (LTD– Low Temperature Degradation) on the surface micro-morphology, phase transformation (t-m) and mechanical behavior (flexural strength and structural reliability) of a Y-TZP ceramic; 2nd study- to evaluate the effect of postprocessing surface treatments and associations (polishing, heat treatment, glazing, polishing + heat treatment and polishing + glazing) on the surface micro-morphology, phase transformation (t-m) and fatigue behavior of Y-TZP ceramic; 3rd study- to evaluate the effect of different pre-sintering fabrication processing techniques (CAD/CAM milling x in-lab fabrication processing techniques) on the outcomes aforementioned. For three studies, discs of Y-TZP ceramic were manufactured according to ISO: 6872-2008. To the first study, the specimens were divided into 10 groups according to the aging (with or without) and surface treatment (Ctrl; “as-sintered”; Ctrl + Aut: ‘as-sintered” + aging; Gr: ground with diamond bur; Gr + Aut: ground with diamond bur + aging; Gr + HT: ground with diamond bur + heat treatment; Gr + HT + Aut: ground with diamond bur + heat treatment+ aging; Gr + Pol: ground with diamond bur + polishing; Gr + Pol + Aut: ground with diamond bur + polishing + aging; Gr + Gl: ground with diamond bur + glazing; Gr + Gl + Aut: ground with diamond bur + glazing + aging. To the second study, the specimens were divided into 7 groups: Ctrl: “as-sintered”; Gr: ground; Gr + HT: ground and heat treatment; Gr + Pol: ground and polishing; Gr + Pol + HT: ground, polishing and heat treatment; Gr + Gl: ground and glazing; Gr + Pol + Gl: ground, polishing and glazing. To the third study, the specimens were divided into 5 groups: Polished: polishing group (conventional process); Machined: CAD/CAM milling; Fine, Xfine and SiC: fabrication using a cutting machine followed by grinding with diamond bur fine, xfine and 220-grit silicon carbide, respectively. All of the grinding procedures of the third study were performed before sintering. Regarding the first study, it observed that polishing generated higher characteristic strength than the other surface treatments and reduced the surface roughness. These findings corroborate to ones from the second study: the polishing promoted higher fatigue strength. According to the third study, the grinding with fine diamond burs (46μm) before sintering showed to be the best protocol to mimic the surface and the mechanical behavior of Y-TZP ceramic milled by CAD/CAM.